TINJAUAN YURIDIS TERHADAP PEMBERIAN GRASI BAGI TERPIDANA NARKOTIKA DI INDONESIA ( Study Kasus Schapelle Leigh Corby ) - Desi Anggraeni '; Mukhlis Ridwan '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
ABSTRACTGranting clemency 5 (five years) agains tAustralian citizen Schapelle Leigh Corby by Presidentcaused controversyfromvarious parties. Althoughthe granting of pardonis aprerogative of the presidentin accordancewithArticle14 paragraph(1) of Actof 1945andLaw No.5 of 2010concerning Amendmentto Law Number22Year 2002 onclemency, clemencybutare considered lessappropriate becausenarcoticscrimeisaseriouscrimeandIndonesia isa party tothe Conventionof the United Nationsandhas ratified the conventionthroughLaw No.7of 1997is nowset inAct No.35 of 2009 onnarcotics.The purposeofthis study, to knowthe procedureforgrantingclemencyCorbyconvictedof narcoticsandtoknow the basicconsideration ofthe President ingranting pardonstoconvicteddrugCorby.The research wasdone byusing anormativeapproach, namely the principles of law, the typeof datain this researchis to useprimary legal materialsof the Constitution ofthe Republic of IndonesiaYear 1945, andthe Act, secondarylegalmaterials(books relating toresultsresearchthat isgrantingpardons toconvictednarcoticsandthe datafromthe internet) andtertiarylegal materials(Dictionary of Indonesian Language), data collection techniquesin this studywith thestudy ofLibrarianshipanddata analysisusing thedeductivemethodisa way ofdrawing conclusionsfromthe propositionthatgeneralto thespecific.From the research problem , there are two main things that can be inferred . First , the procedure and the process of granting pardons given to court decisions that have permanent legal difficult decision and was taken after long consideration , and a sense of humanity and justice Consider , for Corby often have sickly . Suggestions author , First , the good Supreme Court imposes limits to the President to use his power . Second , the President may grant clemency to provide basic reason juridical considerations clearly , firmly and accountable as well as taking into consideration the relevant agencies .Keywords: Judicial Review-GrantingClemency-ConvictedNarcotics